The use of special education teachers in Makkah Al-Mukarramah for electronic educational games as an educational medium and the obstacles to their use - Al-Subhi, Waed Juma Rashid; Alshaaeir, Abdullah Musharraf (Journal of Educational and Psychological Sciences, 2023)
The study aimed to find out the degree of use of electronic educational games by special education teachers in Makkah Al-Mukarramah and the obstacles to their use from their point of view. The researcher used the descriptive analytical approach, and the tool was a questionnaire; It was distributed to a deliberate sample of (264) female teachers. They represent (91%) of the special education teachers in Makkah Al-Mukarramah. The results of the study showed that the degree of use of special education teachers in Makkah Al-Mukarramah for electronic educational games as an educational medium came at an average of (4.27 out of 5) with a degree (very high) and that there are obstacles to their use of electronic educational games as an educational medium that came with an average (3.72 out of 5) with a (high) degree, and there were no statistically significant differences at the level of significance (α≤0.05)) between the averages of the study sample’s estimates about the degree of their use. Results The researcher recommended the need to work to reduce the teaching burden of female teachers, and to encourage and motivate them to use them, as suggested Complementary studies on the subject.